Binge drinking, alcohol outlet density and associated factors: a multilevel analysis among adolescents in Belo Horizonte, Minas Gerais State, Brazil - Juliana Gabrielle Martins; Mariana Oliveira Guimarães; Kelly Oliva Jorge; Carlos José de Paula Silva; Raquel Conceição Ferreira; Isabela Almeida Pordeus; Ichiro Kawachi; Patrícia Maria Pereira de Araújo Zarzar (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2019)
Our study sought to evaluate the prevalence of binge drinking in adolescents and its association with density of alcohol outlets around schools. This cross-sectional study was conducted in Belo Horizonte, Minas Gerais State, Brazil, with 436 high-school students aged between 17 and 19 and enrolled in 18 public and private schools. The students completed the Alcohol Use Disorder Identification Test (AUDIT-C), consisting of questions about alcohol consumption by parents and siblings, and socioeconomic status (type of school, mother's education level). Data from geographic information systems were used to estimate the density of alcohol outlets around schools participating. The association between exploratory variables and binge drinking was investigated using multilevel logistic regression analysis (p < 0.05) with random intercepts and fixed slopes. A three-step sequential modeling strategy was adopted. The prevalence of binge drinking was 39.9%. The alcohol consumption among adolescents was lower for those studying in areas with low density of alcohol outlets around schools (OR = 0.32; 95%CI: 0.14; 0.73) and the consumption of alcohol by mothers was associated with binge drinking among adolescents (OR = 1.94; 95%CI: 1.14; 3.30). Our study concluded that binge drinking among adolescents was associated with density of alcohol outlets around the schools and mother's alcohol consumption.